Trends and patterns of benzodiazepines and Z‐drugs prescriptions in Australian general practice: A national study (2011–2018). (10th October 2022) - Gonzalez‐Chica, David; Begum, Mumtaz; Bernardo, Carla; Hoon, Elizabeth; Sweetman, Alexander; Stocks, Nigel
Abstract: Introduction: We aimed to explore trends and sociodemographic patterns in benzodiazepine (BZD) (by half‐life) and Z‐drugs prescribing in Australian general practice. Methods: This open cohort study used de‐identified electronic health records of 1.4 million patients (50, 812, 413 consultations) from 402 Australian practices (MedicineInsight 2011–2018). Annual prescribing frequency and changes over time were estimated according to sex, age, socioeconomic position and rurality. Results: Between 2011 and 2018, the prescribing of very short‐acting BZD increased from 0.10 to 0.29 per 1000 consultations (average annual change +17.2% [95% CI 9.6; 25.3]), while it declined for short‐intermediate (from 38.5 to 26.6 per 1000 consultations; annual change −5.1% [95% CI −5.6; −4.5]), long‐acting BZD (from 24.1 to 21.6 per 1000 consultation; annual change −1.5% [95% CI −2.2; −0.8]) and Z‐drugs (from 4.6 to 4.0 per 1000 consultations; annual change −1.9% [95% CI −3.0; −0.7]). Short‐intermediate‐acting BZD prescribing was three times more frequent among women aged 65+ years than younger women, and long‐acting BZD three‐to‐four times more likely among younger than older men. Z‐drugs prescribing was higher among women aged 45–64 years than younger or older females. Short‐intermediate‐ and long‐acting BZD were more likely prescribed for patients from more disadvantaged areas, and Z‐drugs in more advantaged areas. There were no disparities by rurality. Discussion and Conclusions: Although most BZD and Z‐drugs prescriptions declined over time, short‐intermediate BZD prescriptions remained higher among older women and long‐acting BZD more frequent among younger men, especially for those living in more disadvantaged areas. Targeted interventions could reduce the prescribing of BZD and Z‐drugs in these groups.